Pengaruh Motivasi Kerja Lingkungan Kerja Dan Budaya Kerja Terhadap Kinerja Pegawai Perusahaan Pembangkit Listrik Tenaga Diesel (PLTD) Di Desa Fanating Kecamatan Teluk Mutiara Kabupaten Alor - Onmau, Suku Abui Neng; Hermayanti, Hermayanti; Gorang, Alvonso Fanisius; Peny, Theresia Lounggina Luisa (Peneliti.net, 2023)
Abui Neng Onmau Tribe (2023) Thesis Title The influence of work motivation, work environment and work culture on employee performance at a Diesel Power Plant (PLTD) company, Fanating Village, Teluk Mutiata District, Alor Regency supervisor I. Theresia L. L Peny. SE. MM. and supervisor II : Dr. Hermayanti SE., MM. This study aims to determine the effect of work motivation, work environment and work culture on employee performance at a Diesel Power Plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. . This study uses population primary data and the sample is employee employees on the influence of work motivation, work environment and work culture on employee performance at a Diesel Power Plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency, totaling 35 people. And the sampling technique in this study is a saturated sample. The statistical method used in this study is multiple linear regression. The results of this study indicate that: (1). partially the work motivation variable has a significance value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the work motivation variable partially has a positive effect on employee performance at employees at the Diesel Power Plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency. (2). partially the work environment variable has a significant value of 0.011 or 1.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the work environment variable partially has a positive effect on employee performance at Diesel Power Plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency (3). partially the work culture variable has a significant value of 0.002 or 0.2% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the work discipline variable partially has a positive effect on employee performance at a Diesel Power Plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency. (4). simultaneously the variables of work motivation, work environment and work culture have a positive effect on employee performance in a diesel power plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency H4 which states that work motivation variables work environment and work culture have a positive effect on employee performance in the Diesel Power Plant (PLTD) company in Fanating Village, Teluk Mutiara District, Alor Regency (5). The magnitude of the influence of the variable work motivation, work environment and work culture on the performance of employees of the diesel power plant company (PLTD) in Fanating Village, Teluk Mutiara District, Alor Regency, this type of research is 82.2%, this study simultaneously received H5.